World Journal of Surgical Oncology - Pandey, Manoj
World Journal of Surgical Oncology publishes articles related to surgical oncology and its allied subjects, such as epidemiology, cancer research, biomarkers, prevention, pathology, radiology, cancer treatment, clinical trials, multimodality treatment and molecular biology. Emphasis is placed on original research articles. The journal also publishes significant clinical case reports, as well as balanced and timely reviews on selected topics. Oncology is a multidisciplinary super-speciality of which surgical oncology forms an integral component, especially with solid tumors. Surgical oncologists around the world are involved in research extending from detecting the mechanisms underlying the causation of cancer, to its treatment and prevention. The role of a surgical oncologist extends across the whole continuum of care. With continued developments in diagnosis and treatment, the role of a surgical oncologist is ever-changing. Hence, World Journal of Surgical Oncology aims to keep readers abreast with latest developments that will ultimately influence the work of surgical oncologists.